NORMATIVE ASPECTS OF HUMAN RIGHTS PROTECTION IN THE AGE OF ARTIFICIAL INTELLIGENCE - Popović, Sanja (Political Review, 2026)
Artificial intelligence, operating within its comprehensive physical and omnipresent digital dimensions, is fundamentally transforming numerous intimate and public aspects of our everyday lives. Its constant and increasingly pervasive presence, reflected in the growing number of devices and applications, illustrates a rising societal tendency to place full and ever-greater trust in complex algorithms in the pursuit of rapid advice and efficient solutions to a wide range of personal and professional problems and tasks. Within public discourse, its undeniable potential to stimulate economic growth, accelerate technological progress, and generate other measurable benefits for society as a whole is frequently celebrated with enthusiasm. Yet, overshadowed by these promising narratives, significant challenges that inevitably confront the fundamental rights and freedoms of individuals in this new technological environment are often largely overlooked. In the following text, the author seeks to carefully and systematically acquaint the reader with the foundational concept of human rights as a fundamental achievement of civilization, their rich theoretical background shaped throughout the history of philosophical and legal thought, as well as their crucial role in the ongoing and increasingly intense debates on the ethical, legal, and social implications of contemporary artificial intelligence. Among the numerous complex and unresolved questions inevitably raised by the rapid development and ever-expanding application of artificial intelligence, particularly in the sensitive domain of human rights, the author will identify and critically examine those rights that, according to many experts and observers, are most endangered and are increasingly emerging at the very center of attention. This includes not only the focus of the academic and scientific communities but also the concern of the broader public. These rights are: the right to privacy in the digital age, the principle of non-discrimination in the context of algorithmic decision-making, freedom of expression in the online sphere, and the right to work, which is inextricably linked to the increasingly pressing issue of potential mass unemployment and the growing inequality in the distribution of economic wealth within society.